Implementation of Design Thinking Concepts in Eco-Fashion Product Design - Gunawan, Arien Arianti; Putri, Mediany Kriseka; S. Putri, Ifa Nadhifah (Fakultas Ekonomi dan Bisnis, Telkom University., 2023)
The study aims to determine how green design thinking and entrepreneurship concepts can be applied to fashion products made from recycled materials. This study uses a design thinking approach and a qualitative approach that aims to gain a deep understanding, develop theoretical foundations, and describe the reality of the research scope. The technique is in the form of collecting data from waste banks, garbage collectors, and several people who are competent in the fashion sector by conducting in-depth interviews. The combination of design thinking and green entrepreneurship can have a positive impact; problem-solving can be done through the design thinking stage to innovate in business while supporting the environmentally friendly movement. Products derived from